ISLAM SASAK: POLA KEBERAGAMAAN KOMUNITAS ISLAM LOKAL DI LOMBOK - Ahmad Amir Aziz (Millah: Journal of Religious Studies, 2009)
This paper aims to describe the characteristic appears in the religious identity of Sasak community in Lombok, and to understand Wetu Telu that was considered an uncompleted process of islamization by presently most Muslims in the region. According to the writer Islam Sasak, including Waktu Lima as promoted by tuan guru, is combination of tradition, cultural, and religious values. This may be seen from various rituals which tend to emphasize negotiation between Islamic texts and social contexts. Islamic local leaders have succeeded to make the opened-religiosity system like ritual of muludan. Another point of view, merariq tradition still accommodated pesuke which is the dominant culture in Sasak. Based on this view the writer underline that dialectical processes between Islam and Sasak tradition still going on through various local traditions from the past to the present.